The Threat To Democracy From The Environmental Law After The Election of The President And Vice President For The Period 2024-2029: A Review of Critical Theory - Cut Zulfahnur Syafitri; Rusli, Budiman; Deliarnoor, Nandang Alamsah (Dinasti Research, 2024)
One of the most criticized arrangements in the Job Creation Law is its regulation in the environmental sector which changes several provisions in Law No. 32/2009 on Environmental Law. The regulation in the Job Creation Law in the environmental sector is the legal politics of the Jokowi administration and will be continued by the government that won the 2024-2029 presidential election. This arrangement can be explained using critical theory. This research was prepared with the aim of knowing the threat to democracy from the Job Creation Law in the environmental sector, which in its ratification caused pros and cons in the Prabowo-Gibran Government era. This research uses normative legal research with a statutory approach and conceptual approach. The results show that the Job Creation Law in the environmental sector is more likely to reduce community participation in environmental approval, which is one indicator of the realization of democracy in state administration. This regulation is a threat to democracy after the 2024-2029 presidential election because the winner of the 2024-2029 presidential election has a tendency to continue the previous government's program.